PENGARUH HARGA, KUALITAS PRODUK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS PELANGGAN PRODUK MEREK JIMS HONEY DI KOTA BANJARBARU - Kiranti Dwi Putri; Maryono; Irwansyah; Rizki Muslim Hidayat (Smart Business Journal (SBJ), 2025)
This study aims to analyze the influence of price, product quality, and brand trust on customer loyalty toward Jims Honey products in Banjarbaru City. The research method used is quantitative with a survey approach, involving 100 respondents selected through purposive sampling. The research instrument was tested for validity and reliability, and the data were analyzed using multiple linear regression and classical assumption tests. The results show that price, product quality, and brand trust have a simultaneous and significant effect on customer loyalty. Partially, all three independent variables also show a significant influence, with brand trust emerging as the dominant variable. The research model is able to explain 56.7% of the variation in customer loyalty (R² = 0.567). These findings indicate that customer loyalty to local fashion products such as Jims Honey is influenced by a combination of fair price perception, adequate product quality, and trust in the brand. The practical implication of this research is the importance of marketing strategies that focus on strengthening product value and building sustainable brand trust. This study also provides a theoretical contribution to the literature on consumer behavior and customer loyalty in the local fashion retail sector. Future research is expected to consider other variables, such as customer satisfaction or shopping experience, to gain a more comprehensive understanding.